2010
DOI: 10.1002/mop.25366
|View full text |Cite
|
Sign up to set email alerts
|

2.4 GHz bio‐radar system with improved performance by using phase‐locked loop

Abstract: Tilted-and axialbeam formation by a single-arm rectangular spiral antenna with compact dielectric substrate and conducting plane, IEEE Trans ABSTRACT: This letter presents a novel bio-radar system with phaselocked loop (PLL) for noncontact measurement of vital sign. As the leakage of the phase noise of local oscillator (LO) through antenna is dominant factor for the distances larger than about 30 cm, the performance of a bio-radar system can be improved with the PLL employment. The proposed bio-radar and PLL a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Therefore, alternative solutions for single antenna implementation can be explored. One possible solution is sharing the same radiating aperture using a CP antenna and using opposite polarizations for TX and RX functions [16,17,20,21]. For example, in [17], a single antenna with CP and operating at 24 GHz, was shared by TX and RX.…”
Section: Single Antenna For Tx/rxmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, alternative solutions for single antenna implementation can be explored. One possible solution is sharing the same radiating aperture using a CP antenna and using opposite polarizations for TX and RX functions [16,17,20,21]. For example, in [17], a single antenna with CP and operating at 24 GHz, was shared by TX and RX.…”
Section: Single Antenna For Tx/rxmentioning
confidence: 99%
“…The same approach was used in [20], where a bio-radar system is presented with a phase-locked loop and uses a single antenna for TX and RX. In this work, the authors have developed a circular-polarized annular ring microstrip antenna, with RHCP at transmitting mode and LHCP at receiving mode.…”
Section: Single Antenna For Tx/rxmentioning
confidence: 99%
“…The experimental data revealed that the presented system can detect human cardiopulmonary activity within a normal detection distance using optimal pulse bias conditions. Compared with the sensor using the PA , power consumption of this presented sensor can be further reduced and other performances are in acceptable ranges.…”
Section: Introductionmentioning
confidence: 98%
“…For long‐term remote sensing, low power dissipation for a wireless sensor is required to detect human cardiopulmonary activity without interference. The vital sign wireless sensor usually uses direct current (DC) bias to maintain information integrity, providing adequate accuracy. When a power amplifier (PA) is used to increase signal strength for improving sensitivity , the sensor will continuously consume large DC power.…”
Section: Introductionmentioning
confidence: 99%
“…We have also introduced a circular polarized antenna to reduce size and to allow use of a single antenna for bio-radar applications [12,13]. In the present paper, a MIMO bio-radar system is introduced that consists of two bio-radar system sharing identical VCO with a PLL and new concept of direction finding of human target based on phase difference between two receivers is presented.…”
Section: -1 System Configurationmentioning
confidence: 99%